Application of Cogon Grass (Imperata cylindrica) as Biosorbent in Diesel-Filter System for Oil Spill Removal - Khalid, Farah Eryssa; Ahmad, Siti Aqlima; Zakaria, Nur Nadhirah; Shaharuddin, Noor Azmi; Sabri, Suriana; Azmi, Alyza Azzura; Khalil, Khalilah Abdul; Verasoundarapandian, Gayathiri; Gomez Fuentes, Claudio German; Zulkharnain, Azham (My University, 2021)
Imperata cylindrica, often known as cogon grass, is a low-cost and useful sorbent for absorbing oil and optimising processes. The effects of temperature, time, packing density and oil concentration on oil absorption efficiency were investigated and optimised utilising one-factor-at-a-time (OFAT) and response surface methodology (RSM) approaches. Temperature and oil concentration are two important variables in the oil absorption process. Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM) analysis were used to characterise cogon grass. After treatment and oil absorption, the FTIR method indicated new formation and deformation of functional groups, while SEM revealed changes in the surface and texture of cogon grass, including a roughened and jagged surface. Validation of the RSM model yielded 93.54% efficiency with 22.45 mL oil absorbed at 128&DEG;C temperature and 36 (v/v)% oil concentration while keeping packing density and time constant at 30 min and 0.20 g/cm(3), respectively. This study may provide an insight into the usefulness of a statistical approach to maximise the oil absorption of cogon grass as an oil sorbent.
Keywords: imperata cylindrica; oil absorption efficiency; one-factor-at-a-time (ofat); response surface methodology (rsm)